Effectiveness of Administration of Papaya Leaf Capsule Extract (Carica Papaya) and Moringa Leaves (Moringa Oleifera) on Increasing Prolactin Hormones in Breastfeeding Mothers - Mawaddah, Sofia (EMBRIO: Jurnal Kebidanan, 2024)
This research aimed to determine the effectiveness of administering papaya (Carica Papaya) and Moringa leaf (Moringa oleifera) capsule extracts on prolactin hormone levels in breastfeeding mothers in PMB M Palangka Raya City. The research used was Quasy Experimental, Two Group Pretest – Posttest design (two groups pretest – posttest). The sampling technique used was purposive sampling, with a total sample of 66 respondents who met or met the inclusion criteria. The statistical test used is the Independent T-test. Based on the significance results, the resulting Z statistic is -3.531 with a probability of 0.000. This means that probability less than significance level (alpha equals 5percent). Thus, it can be stated that there is a significant difference in the levels of the hormone prolactin in breastfeeding mothers in PMB M Palangka Raya City before and after administering Moringa leaf capsule extract.